THE RIGHT TO DEMOCRACY ARRANGEMENT UNDER INTERNATIONAL LAW - Rika Kurniaty (RechtIdee, 2019)
In the historical context, during the Cold War, due to the tension of ideology between countries, the link between international law and the notion of democracy only received few discussions and interest by international law scholars. The fall of communism in the early 1990s has put liberal democracy - as the only legal system of government - back on the global agenda. The victory of democracy throughout the world quickly led to the claim that there is now a right to democracy in international legal instruments and the existence of democracy as a guiding principle in general international law. However, the word "democracy" does not appear in the Charter of the United Nations and in the Covenant of the League of Nations. There is no standard textbook on international law that contains chapters on democracy. The International Court of Justice does not base its decisions on applying the principles of democratic rule. If one does not look beyond the pillars of international law, one could conclude that democracy is irrelevant. In maintaining that all communities are entitled to democratic governance, this paper will examine arrangements for the right to democracy in international law, especially under the Universal Declaration of Human Rights, which is recognized by the international community.